Influence of Religiopoliticology and Duressed Womankind: Perspective Bangladesh - Hossain, Md. Kohinoor (International Journal of Islamic Business & Management, 2018)
The world is continuing at its own orbiting and fugitive for the adamboma or bomb of Adam in the womankind and mankind, who are classified into the four generations, and they are religious world, nonreligious world, scientist world and humanitarian world but the people of Bangladesh are in the same kind like the world people to find out God and how they use religions, which is that have discussed by this paper. Bangladesh is a land of ice-aged. It has ancient beliefs, fear, and faiths, which are convinced on the inter-ward eyes, concise and understanding. The original people of her are Non-Aryan. Aryans come to here from the Persian and Middle East countries in the caravan of the rules of the chronology, many foreigners who come to Bengal, they are Greeks, Europeans, and Africans, all of them capture Bengali and they rule Bengal. They snatch away their own land, language, culture, economics, politics, beliefs, and love-nets. Here makes up all official religions, someone is downtrodden by them who remake apartheid in the society of Bengal, this is why they are de-throne from their own land, and they try to live as a freedom where they make up folk-religions. Bengalees learn the foreigners’ religions and they convert into these official religions. The rulers of Bengal rule them as following the religious doctrines only for getting votes when they need to play political power playing and that is why they use them. They use many styles of God theory. The Bengalees, they can how to use the orders of God that will be sought out in this paper. This paper seeks that how the cultic dynamics radicalization runs in Bangladesh and what is the best concept of God in Bangladesh. All people live in equal in the land of God in Bangladesh that empirically applies, for the globe.